Case Study: Converting Paper-based Case Report Forms to an Electronic Format (e-CRF) with ACASI Self-Report Integration - Mierzwa, Stan; Souidi, Samir; Akello, Carolyne; Etima, Juliane; Ssebagala, Richard; Nolan, Monica; Kabwigu, Samuel; Nakablito, Clemensia (Online journal of public health informatics, 2017)
This paper will discuss the integration of electronic Case Report Forms (e-CRFs) into an already existing Android-based Audio Computer-Assisted Self-Interview (ACASI) software solution that was developed for a public health project in Kampala, Uganda, the technical outcome results, and lessons learned that may be useful to other projects requiring or considering such a technology solution. The developed product can function without a connection to the Internet and allows for synchronizing collected data once connectivity is possible. Previously, only paper-based CRFs were utilized at the Uganda project site. A subset or select group of CRFs were targeted for integration with ACASI in order to test feasibility and success. Survey volume, error rate, and acceptance of the system, as well as the operational and technical design of the solution, will be discussed.
Keywords: Self-Report Data Collection; Case Report Forms; CRF; e-CRF; Tablets; Android; Clinical trials; Feature integration